Assessing individual KM enablers towards effective KM practices / Muhammad Zaidie Bardan and Mazwani Ayu Mazlan. - Bardan, Muhammad Zaidie; Mazlan, Mazwani Ayu (Universiti Teknologi MARA Cawangan Selangor, 2018)
Implementation of knowledge management in organization practices is generally perceived as giving competitive advantage and expanding number of organization are consolidating knowledge management strategy. Organizations are interested on knowledge management to support the effectiveness, increase the profitability and efficiency of their administration. Then again, inside the research community, knowledge management is considered as catalyst or understanding the part of knowledge in an organization. The consistent advancement in the field of knowledge management has prompted various basic components being highlighted in the literature, which include organization culture variables like collaboration, trust, learning, and information technology.